2021
DOI: 10.3389/frobt.2021.648485
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Framework Towards the Tele-Rehabilitation of Balance Control Skills

Abstract: Mobility has been one of the most impacted aspects of human life due to the spread of the COVID-19 pandemic. Home confinement, the lack of access to physical rehabilitation, and prolonged immobilization of COVID-19-positive patients within hospitals are three major factors that affected the mobility of the general population world-wide. Balance is one key indicator to monitor the possible movement disorders that may arise both during the COVID-19 pandemic and in the coming future post-COVID-19. A systematic qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…This will enable remote assessment, rehabilitation and care, with an individualized approach and less time and cost. This opens up a new avenue for the development of intelligent (including robotic) solutions for home rehabilitation [ 36 ].Virtual reality (VR) is a well-established technology in medicine but comprehensive studies on the possible applications of VR in posture measurement are scarce. A review of 21 studies [ 37 ] confirmed that virtual reality is often used as an additional visual stimulus in the assessment of static and dynamic posturography, with researchers particularly hopeful about VR-based postural assessment in a head-mounted display (HMD VR) [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This will enable remote assessment, rehabilitation and care, with an individualized approach and less time and cost. This opens up a new avenue for the development of intelligent (including robotic) solutions for home rehabilitation [ 36 ].Virtual reality (VR) is a well-established technology in medicine but comprehensive studies on the possible applications of VR in posture measurement are scarce. A review of 21 studies [ 37 ] confirmed that virtual reality is often used as an additional visual stimulus in the assessment of static and dynamic posturography, with researchers particularly hopeful about VR-based postural assessment in a head-mounted display (HMD VR) [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic balance training was performed twice a week for eight training sessions using the CD and its complementary training software COORDI (MFT Bodyteamwork). The CD is an established tool concerning balance performance assessment and has been used in a number of studies ( Bayer et al, 2017 ; Seidel et al, 2017 ; Akbas and Mummolo, 2021 ). It is made up of a circular platform (440mm diameter) with an inclination sensor that is connected to a fixed base plate via an elastic center connection ( Figure 1C ).…”
Section: Methodsmentioning
confidence: 99%